Electrochemical study of oxaferrocene cryptands and their complexation with barium and sodium ions. - Pagels, M; Meredith, A; Jones, T; Compton, R; Plenio, H; Jiang, L (2005)
The electrochemical behaviour and cation recognition properties of two oxaferrocene cryptand ligands, 1,1'-[(1,4,10-trioxa-7,13-diazacyclopentadecane-7,13-diyl)diethoxy]-3,3',4,4'-tetraphenylferrocene and 1,1'-[(1,4,10,13-tetraoxa-7,16-diazacyclooctadecane-7,16-diyl)diethoxy]-3,3',4,4'-tetraphenylferrocene, have been characterized in acetonitrile in the presence of Ba(2+) and Na(+) by cyclic voltammetry, square wave voltammetry and a rotating disc electrode. The changes in the redox signals for the cryptates at varying concentrations of the target cations are used as a direct measure of the electronic coupling between the two units, leading to the conclusion that the cryptate formation process proceeds in multiple stages and the ligand offers several binding sites in the complex.